Proactive measures of governmental debt guarantees to facilitate Public-Private Partnerships project - Tserng, Hui Ping; Ho, Shih-Ping; Chou, Jui-Sheng; Lin, Chieh (Journal of Civil Engineering and Management, 2014)
Governmental Debt Guarantees (GDGs) are often used to encourage involvement by promoters and financial institutions in Public-Private Partnerships (PPP) projects. However, even after demonstrating the bankability of a project and reducing debt cost, the success of the project may be prevented by the lack of long-term commitment from shareholders. Equity contributions by promoters in the project company may be recovered from earnings on short-term construction activities. Based on lesson learned from early PPP projects with GDG, the hold-up problem for government in the view of transaction cost economic (TCE) theory may worsen if the designed contractual structure does not adequately manage opportunistic behaviours from promoters. This study empirically examined the effects of a structured GDG mechanism with particular complementary measures applied in joint projects to develop the Taipei Mass Rapid Transit (MRT) stations. A GDG game model was then applied to bridge the theoretical gap based on the Taipei MRT experience. The analysis shows that requiring the promoter to provide sufficient equity and ensuring the commitment of the lender to provide the loan are the appropriate proactive measures. This study demonstrates its practical value for policy makers by combining case study, TCE and game theory in contractual issues.